Hubungan Status Gizi Dengan Kejadian Anemia Pada Ibu Hamil Trimester III di Klinik Aminah Amin Samarinda Tahun 2018 - Nursyahid Siregar; Azhari Azhari; Nursari Abdul Syukur (Husada Mahakam, 2019)
Abstract Background: Anemia of pregnancy is called "potential danger to mother and child" so that anaemia requires serious attention from all concerned parties in terms of health services (Manuaba, 2010). Impact of anaemia in pregnant women is increasing morbidity rate including bleeding, premature rupture of membrane, risk of low birth weight babies (BBLR), and is one of the main causes of maternal deaths that originate in anaemia (Arisman, 2010). Based on the results of preliminary studies at Aminah Amin Clinic in July - December 2017 there are 513-trimester pregnant women III and 74 pregnant women have anaemia. Objective:This study aims to determine the relationship of nutritional status with the incidence of anaemia in trimester pregnant women III Amin Sininda Aminah Clinic in 2018. Method: the design of this study is crossectional, the population is pregnant women who visit at Aminah Aminah Clinic. Sampling technique with total sampling of 53-trimester pregnant women III. Results: The results of this study showed that there was a significant relationship between nutritional status and the incidence of anaemia in the third-trimester pregnant women (p-value =0,004) with α = 0,05. Conclusion: There is a significant correlation between nutritional status and the incidence of anaemia in pregnant mother of trimester III at Aminah Aminah Clinic in 2018. Keywords: Nutritional status, incidence of anaemia, pregnant mother of third trimester